2015
DOI: 10.1007/s11661-015-2780-0
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Characterization and Thermal Analysis of Aluminum Alloy B206 During Solidification

Abstract: The solidification kinetics of a high strength B206 aluminum casting alloy as a function of cooling rates between 1 and 15 K/min has been characterized through a combination of differential scanning calorimetry (DSC), scanning electron microscopy (SEM), and optical microscopy. Three different peaks were detected in the DSC analysis, which corresponded to the nucleation of an α-Al solid solution, an Al-Cu-Fe intermetallic and the eutectic phases. The presence of these phases was confirmed using a coupled scanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Consequently, if the values of A and x are previously known, then the value of α at an arbitrary cooling rate is calculable using eq. (23). Figure 12 shows the relation between the cooling rate and DAS II measured in the current study.…”
Section: Calculation Of the Solidi Cation Parameter α At Anmentioning
confidence: 73%
See 1 more Smart Citation
“…Consequently, if the values of A and x are previously known, then the value of α at an arbitrary cooling rate is calculable using eq. (23). Figure 12 shows the relation between the cooling rate and DAS II measured in the current study.…”
Section: Calculation Of the Solidi Cation Parameter α At Anmentioning
confidence: 73%
“…Viscoplastic properties are assumed to be dependent on the solid fraction in a partially solidi ed state, as reported earlier in the literature 2,14,18) . Increase in the cooling rate is known to promote microsegregation 19,20) and to affect relations between temperature and solid fraction [21][22][23] during solidi cation. By considering the effect described above using a microsegregation model, the current study predicts viscoplastic properties at an intended cooling rate based on previously reported viscoplastic properties 17) .…”
Section: Predicting Cooling Rate Dependence Of Viscoplastic Propertiementioning
confidence: 99%
“…The values obtained from experiments differed slightly from those obtained from theoretical calculations for ternary alloys; these differences can be attributed to different rates of solidification/heating in DSC experiment. [19,20,23] However, this difference was very large for the solidus temperature of AM6 binary alloy, which was around 577°C in DSC experiment, compared to 451°C calculated theoretically (Table III). It was found that enthalpy of fusion of the tested alloys increased with increasing Si content.…”
Section: Resultsmentioning
confidence: 78%
“…This necessity is overemphasized in the case of 206-type aluminum alloys (i.e., A206 and B206), due to their heat treatment complexity which is exerted by the presence of Cu-rich intermetallic phases. [5][6][7] The Cu-rich phases hold lower electrochemical potential and lower galvanic corrosion resistance, thereby, corroding faster than its counterparts in Al-Cu series. Some of the performed researches regarding the severe plastic deformation of Al alloys have focused on the effects of processing parameters such as the accumulative strain, [8] strain path, [9] strain rate, [10] and the inter-pass treatments.…”
Section: Introductionmentioning
confidence: 99%